ENTREPRENEURSHIP SKILL SISWA MELALUI PELATIHAN BIOENTREPRENEURSHIP - Nur Hayati; Noer Af’idah; Andri Wahyu Wijayadi; Lina Arifah Fitriyah (Prosiding Seminar Nasional Sains, Teknologi, Ekonomi, Pendidikan dan Keagamaan (SAINSTEKNOPAK), 2023)
Abstract Entrepreneurship skill is one of the 21st century skills that is important for students to have. One effort to improve entrepreneurship skills in students can be done through the bioentrepreneurship learning method. The purpose of this Community Service activity (PKM) is to train students' entrepreneurship skills with bioentrepreneurship. The target of this PKM is students of MA SSKH Jombang class XII IPA. Data collection through interviews, observation and tests. This PKM activity gave results in the form of increasing student entrepreneurship skills before and after PKM. There was an increase in the average knowledge score from 66.3 to 74.5 and students' skills increased with an average score of 65.9 to 77.2. Keywords: Entrepreneurship skill, Bioentrepreneurship Abstrak Entrepreneurship skill merupakan salah satu keterampilan abad ke-21 yang penting dimiliki siswa. Salah satu upaya untuk meningkatkan entrepreneurship skill pada siswa dapat dilakukan melalui metode pembelajaran bioentrepreneurship. Tujuan kegiatan Pengabdian kepada Masyarakat (PKM) ini adalah untuk melatihkan entrepreneurship skill siswa dengan bioentrepreneurship. Sasaran PKM ini adalah siswa MA SSKH Jombang kelas XII IPA. Pengumpulan data melalui metode wawancara, observasi dan tes. Kegiatan PKM ini memberikan hasil berupa peningkatan entrepreneurship skill siswa sebelum dan setelah PKM. Terdapat peningkatan rerata skor pengetahuan dari 66,3 menjadi 74,5 dan keterampilan siswa meningkat dengan rerata skor 65,9 menjadi 77,2. Kata kunci: Entrepreneurship skill, Bioentrepreneurship